1999
DOI: 10.1007/s002470050558
|View full text |Cite
|
Sign up to set email alerts
|

Glutaric aciduria type I: ultrasonographic demonstration of early signs

Abstract: In patients with macrocephaly at birth or rapidly developing within the first weeks of life, US should be performed as the primary imaging modality. Cyst-like bilateral widening of the sylvian fissures is the first sign of GA-I, followed by progressive fronto-temporal and ventricular enlargement. These patients should be screened for GA-I in order to initiate treatment in the asymptomatic stage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
29
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 51 publications
(31 citation statements)
references
References 17 publications
2
29
0
Order By: Relevance
“…50,51 That MR imaging showed some additional findings is also partially because of the time interval between cUS and MR imaging scans reflecting the natural evolution of cerebral lesions in metabolic disorders. 20,43 cUS showed calcification not identified on MR imaging, a useful clue to metabolic diagnoses. GLCs were almost always better seen on cUS, probably caused by partial volume effects from slice thickness.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…50,51 That MR imaging showed some additional findings is also partially because of the time interval between cUS and MR imaging scans reflecting the natural evolution of cerebral lesions in metabolic disorders. 20,43 cUS showed calcification not identified on MR imaging, a useful clue to metabolic diagnoses. GLCs were almost always better seen on cUS, probably caused by partial volume effects from slice thickness.…”
Section: Discussionmentioning
confidence: 99%
“…[10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26] cUS has the advantage that it is readily available on neonatal units when infants are admitted. We have shown in a large cohort of neonates with diagnosed metabolic disorders that cUS detects many abnormalities that support a clinical diagnosis, detects structural abnormalities that lead to further investigations, or depicts ongoing injurious or metabolic processes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The histogenesis of PRC is still unclear. Five major hypotheses have been advocated: heterotopic ovarian tissue 2 , monodermal variant of teratomas 3 , embryonic urogenital remnants 4 , intestinal duplications 5 and celomic metaplasia 6 . In our case, histological and immunohistochemical analyses concluded that the PRC developed from an extraovarian Müllerian issue.…”
Section: Primary Retroperitoneal Endometrial Cystadenocarcinoma Presementioning
confidence: 99%
“…Macrocephaly is the pivotal clinical sign in GA 1 patients in the postnatal period, as it is the earliest and the most consistent sign according to the largest series published 6,7 . Development of macrocephaly usually occurs early in the neonatal period, typically within the first weeks after delivery, but has also been described at birth and even in the prenatal period 5,6 . Radiological findings in GA 1 have been well documented in the neonatal period and in early childhood.…”
mentioning
confidence: 98%